Race And Nation : Ethnic Systems In The Modern World. - Spickard, Paul (Taylor & Francis Ltd., 2004)
Race and Nation is the first book to rigorously compare the various racial and ethnic systems that have developed around the world. The contributors have honed their research and expertise to produce definitive questions in the field, and these.